Three perspectives of architecture - Milašinović Marić, Dijana (Arhitektura i urbanizam, 2023)
Gallery of the Central Military Club, May 17 - June 2, 2023. (Architects: Vasilije Milunović, Jelena Ivanović Vojvodić, and Verica Krstić). Exhibition on the occasion of the Grand Prize of the 54th May Exhibition, awarded by ULUPUDS (Association of Fine Artists and Applied Artists of Serbia)